2011
DOI: 10.1186/1471-2334-11-228
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the virulence of exopolysaccharide-producing Prevotella intermedia to exopolysaccharide non-producing periodontopathic organisms

Abstract: BackgroundEvidence in the literature suggests that exopolysaccharides (EPS) produced by bacterial cells are essential for the expression of virulence in these organisms. Secreted EPSs form the framework in which microbial biofilms are built.MethodsThis study evaluates the role of EPS in Prevotella intermedia for the expression of virulence. This evaluation was accomplished by comparing EPS-producing P. intermedia strains 17 and OD1-16 with non-producing P. intermedia ATCC 25611 and Porphyromonas gingivalis str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…Exopolysaccharides are an essential part of the biofilm matrix (Flemming & Wingender, 2010) and failure to produce exopolysaccharides results in a biofilm formation defect in several bacterial species (Yildiz & Schoolnik, 1999; Koo et al. , 2010; Yamanaka et al. , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Exopolysaccharides are an essential part of the biofilm matrix (Flemming & Wingender, 2010) and failure to produce exopolysaccharides results in a biofilm formation defect in several bacterial species (Yildiz & Schoolnik, 1999; Koo et al. , 2010; Yamanaka et al. , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to produce a biofilm results in enhanced resistance to host defense factors and antimicrobials and is being increasingly recognized as an important virulence property 86 , 87 . Even in the absence of a foreign body, biofilm formation has been shown to be a factor in closed-space infections 88 - 90 . In vitro studies have established that cKP strains are able to produce biofilm, with type 3 fimbriae, 91 , 92 CP and LPS, 93 , 94 amino acid synthesis genes, 95 L -arabinose metabolism, 95 sugar phosphotransferase systems, 94 the type 2 quorum sensing regulatory system, 94 the Lys-R-type regulator oxyR 96 and a putative cell surface protein 95 identified as contributory factors.…”
Section: Pathogenesis Of Infectionmentioning
confidence: 99%
“…EPS is the primary matrix material of biofilm, and viscosity of culture supernatant is an indication of the relative amount of EPS production in the culture (35,37,38). Yamanaka et al (39,40) reported that clinical isolates of P. intermedia designated strain 17 and strain OD1-16 produced mannose-rich EPSs, as revealed by the increased viscosity of the spent culture media. In contrast, the viscosity of the spent culture media of non-biofilm-forming bacteria, including P. intermedia ATCC 25611 and several P. gingivalis strains, was similar to that of the control medium without bacterial inoculation (40).…”
Section: Effect Of Polyp3 Against Planktonic P Intermedia Atcc 4906mentioning
confidence: 99%
“…Yamanaka et al (39,40) reported that clinical isolates of P. intermedia designated strain 17 and strain OD1-16 produced mannose-rich EPSs, as revealed by the increased viscosity of the spent culture media. In contrast, the viscosity of the spent culture media of non-biofilm-forming bacteria, including P. intermedia ATCC 25611 and several P. gingivalis strains, was similar to that of the control medium without bacterial inoculation (40). As observed in our previous study (36), the viscosity of the spent culture medium of P. intermedia ATCC 49046 was significantly increased, at 1.31 Ϯ 0.012 mPa · s, compared to that of the control B-HK medium without bacterial inoculation after 48 h of incubation.…”
Section: Effect Of Polyp3 Against Planktonic P Intermedia Atcc 4906mentioning
confidence: 99%